(untitled) (Neo Science Peer Reviewed Journal, 2022)
This study examined the relationship between work-life balance and employee intention to stay in banking industry in Nigeria. The researcher made use of descriptive research and adopted the quasi-experimental research design. stratified random sampling technique was used in collecting the study data. A total of 270 sample size derived using Taro Yamane formula from an accessible population of 835 employees working at the main branches or head offices of seven selected commercial banks in Nigeria. Data for the study were collected through a questionnaire. A total of 232 copies of filled questionnaires were analysed using univariate analysis (descriptive statistics) and bivariate analysis (inferential statistics). The results showed a positive and significant relationship between the dimensions of work-life balance (workload and perceived organizational support) and the measures of employees’ intention to stay (job satisfaction and organizational commitment). From the study findings, the suggestions proffered by the researcher were; implementing workload management strategies, enhancing organizational support, promoting other forms of work-life balance, and a continuous feedback and improvement system.